Accelerated carbonation of reactive MgO and Portland cement blends under flowing CO2 gas. (February 2020) - Wang, Lei; Chen, Liang; Provis, John L.; Tsang, Daniel C.W.; Poon, Chi Sun
Abstract: The use of MgO-based materials for sequestration of CO2 offers technical advantages and environmental incentives. However, the understanding of accelerated carbonation of MgO-based materials in flowing CO2 gas is limited. This study elucidates the carbonation behaviour of reactive MgO cement (MC) and MgO-Portland binary cement (BC) in a simulated CO2 -rich industrial exhaust. Quantitative X-ray diffraction and thermogravimetric analyses showed that nesquehonite (MgCO3 ·3H2 O) was the major carbonation product in MC pastes, whereas CaCO3 was preferentially generated in BC pastes. The relative humidity of exhaust gas influenced CO2 diffusion and the carbonation rate; 98% humidity facilitated MC carbonation whereas 50% was favourable for BC carbonation. Although CO2 concentration determined the carbonation rate, 10% CO2 gas in the exhaust was sufficient to accelerate carbonation. The carbonation degree and compressive strength of samples cured for 7 days at 10% CO2 were comparable to the values of samples cured for 1 day at 100% CO2 . The presence of acid gases during CO2 curing inhibited the carbonation and hydration processes, but the presence of Portland cement in the BC system gave good compatibility with acids and relieved the inhibitory effect. Desulphurization and denitrification of industrial exhaust gas are nonetheless desirable before CO2 curing. This study builds the foundation for utilising industrial CO2 exhaust to accelerate the carbonation of Mg-based materials. Graphical abstract: Image 1 Highlights: MgO-based cement can sequester and utilise CO2 from industrial exhaust. Relative humidity influenced CO2 diffusion and carbonation rate. 7-d curing with 10% CO2 concentration ensured sufficient carbonation degree. Acid gases in exhaust severely inhibited carbonation and hydration. Binary MgO-Portland cement showed fast carbonation rate and good compatibility with acids.